Postponement Arrangements of Election From The Perspective of The 1945 Constitution of The Republic of Indonesia - Jasi, Askolani; Barthos, Megawati; Santiago, Faisal (Jurnal Indonesia Sosial Sains, 2023)
Abstract. Provisions regarding the postponement of the implementation of elections have been regulated in Article 1 paragraph (2) of the 1945 Constitution of the Republic of Indonesia. Prior to the election, there have always been efforts from several parties who wished that elections could be held in a direct, public, free, honest, fair, and transparent manner. However, this matter was deliberately brought up, so that the implementation of the General Election could be delayed from the previous schedule for some reason. Nevertheless, the implementation of the Election can be postponed, as long as it does not violate the applicable laws and regulations, and has received legal approval based on the results of a Judge's decision in court. The after-effect of the delay in the implementation of the election itself can end in the need for an amendment to Article 22E paragraph (1) of the 1945 Constitution of the Republic of Indonesia. Thus, even though it is legal in the eyes of the law if the implementation of the election is postponed, considering the impact that needs to be caused, all parties, starting from elements of the Legislature and Judiciary in making decisions related to the possibility of holding elections properly and correctly, without political elements involved.